Analysis of Oral Language Variety in the Interaction of Sellers and Buyers in Gamping Market, Sleman Regency, Special Region of Yogyakarta: A Sociolinguistic Study - Desvina Rahmadani; Nina Widyaningsih (Translation and Linguistics (Transling), 2025)
This study aims to analyze the variety of spoken language in the interactions between sellers and buyers at Gamping Market, Sleman Regency, Special Region of Yogyakarta, using a sociolinguistic approach. The research employs a qualitative descriptive method to describe the language varieties emerging in social interactions within the market and identify the factors influencing them. Data were collected through observation, recording, and note-taking techniques and then analyzed to identify the sociolect varieties used by the speakers. The study focuses on the use of the Javanese language by sellers and buyers during transactions. The findings reveal a diverse range of conversations between sellers and buyers at Gamping Market, demonstrating spoken language varieties based on sociolects, specifically acrolect and basilect varieties. Factors such as age, time, place, and gender were found to influence the language varieties used in the interactions between sellers and buyers at Gamping Market.